Drought shocks and its economic impacts on Northeastern Brazil - Branco, Danyelle Karine Santos (2018)
This thesis studies two topics on drought shocks and related economic development using Brazilian data. In the first essay, we study the effects of drought shocks on rural households labor allocation in Northeastern Brazil. We analyze whether rural households use labor allocation to mitigate the effect of drought shocks. While previous studies provide strong evidence that droughts and floods can have an immediate effect on rural income, the extent to which families adjust labor supply to mitigate these effects has been very little investigated. Documenting the quantitative importance of labor supply and other behavioral household responses is crucial for shaping the targeting of policies intended to mitigate the adverse consequences of climate change. Our identification strategy exploits variation in rainfall records over time within municipalities, and relies on the assumption that weather shocks, conditional on municipality and year fixed-effects, are not correlated with other latent determinants of labor supply. We begin our analysis by providing evidence that negative rainfall shocks affect household income in our setting. The results present evidence of a relationship between negative rainfall events and labor time reallocation. We find that drought shocks are significantly associated with lower income derived from one’s main job. This is especially true when we consider income derived from farm activities. Moreover, a higher incidence of drought shocks is significantly associated with increased income from secondary jobs. Our results show that droughts negatively affect hours spent on farm work, whereas it leads to increased supply of non-agricultural jobs. The results show the importance of non-agricultural activities as an autonomous mitigation mechanism. The second essay investigates the impact of drought shocks on educational outcomes of children attending schools in rural Northeastern Brazil. In particular, we assess how droughts may affect students achievement measured by Prova Brasil scores in math and language, a national standardized exam. We believe that there are three main different mechanisms through which weather shocks may affect child schooling: school supply, infant health, and child labor. The findings provide evidence that students from schools that are exposed to drought shocks perform worse on standardized math and Portuguese exams. Our results also suggest that the shock effect seem to be more detrimental for girls and those students with lower educated mothers. We also find suggestive evidence that drought tends to be more harmful to children that study in schools with no cistern or other water storage device. Therefore, investing in basic infrastructure is a low-cost policy strategy in rural areas that may considerably improve school performance. By investigating the potential transmission mechanisms linking weather shocks to school performance, we find that the impact of negative rainfall shocks on child health is an important mechanism driving our results. Exposure to a drought shock increase the hospitalization rate among children. In addition to that, one more drought shock per year is associated to a 4.24% increase in the likelihood of a child being employed. Both health and job-market related effects may be associated to lower school attendance and therefore contribute to poor student achievements. Together, the two essays contribute to a better understanding about the relationship between extreme weather-related events and important economic development issues.